The Influence of the Development of Modified Teaching Materials for Kids Athletics Games on Gross Motor Learning Outcomes of Preschoolers - Eka Cahaya Ningrum; Nurhasan Nurhasan; Nanik Indahwati (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
The gross motor skills of preschoolers are an important part of the child's growth and development process in learning motion. Kids Athletic is one of the intervention references that is thought to be able to develop and improve the gross motor skills of preschool children. However, references to the intervention of the Athletic figurative game in learning need to be developed through game modification. This study aims to analyze the effect of developing modified teaching materials for children's athletic games on gross motor learning outcomes for preschoolers. This type of research is experimental with a pretest and posttest design. 19 students from PAUD TAAM Al-Mubarok Kota Kediri are selected to be part of this study from nonprobability sampling. The results of this study obtained a significance value of 0.00, which is smaller than 0.05. Based on the gross motor skills pretest results are in the BSH (Grow as Expected) level which students are capable to convey the movement, yet they are not capable to perform it properly, and still require teacher assistance. Whereas the gross motor skills post-test results are in the BSB (Well Developed) level which students are capable to perform the movement without teacher assistance. The conclusion of this study is teaching modules developed can influence and improve the learning outcomes of preschool students in terms of their gross motor skills.